Bez przesadow i leku : szkicownik dyletanta - Leitgeber, Boleslaw (Londyn : Polska Fundacja Kulturalna, 1979)
Biography of the Polish diplomat.
Includes index.
Keywords: Leitgeber, Boleslaw; Diplomats -- Poland -- Biography